Comparison of Financial Performance of South Korea's Big 2 Entertainment Companies Case Study SM Entertainment and Hybe Corporation for the Period 2024 - Teefani, Gabrielle; Fidita Karya, Denis (Universitas Dinamika, 2025)
The South Korean entertainment industry is rapidly evolvingthrough Hallyu, with SM Entertainment and HYBE Corporation as the two main companies dominating the industry. These two companies not only manage artists but also execute complex global business strategies, making financial performance analysis highly relevant to understanding their efficiency and competitiveness. This study uses a descriptive quantitative approach with multiple linear regression analysis. The data used are derived from SM Entertainment and HYBE Corporation's 2024 quarterly financial reports, focusing on liquidity, solvency, and profitability ratios against Return on Assets (ROA). The analysis results show that all three financial ratios have a significant simultaneous effect on ROA, but are insignificant partially. Multicollinearity issues were also found between independent variables, which can disrupt model stability. The implications of these findings highlight the importance of management in balancing financial structures holistically. Investors are advised to consider external factors and company strategies holistically, not just financial ratios alone.